A complete course in engineering physic - Roy, Sudipto (S. Chand and Company, 2013)
A complete course in engineering physic / Roy, Sudipto. -- Kolkata: S. Chand and Company, 2013 530 R888e3V2 3rd ed No. of Copies : 1